2014
DOI: 10.1111/ipd.12110
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and dental caries: the association among German children

Abstract: Although iso-BMI was associated with dental caries prevalence and severity, the association between caries increment and iso-BMI did not reach a statistical significance. Overweight/obese children however acquired more additional carious lesions during the follow-up period than children with low-normal weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 28 publications
2
21
0
2
Order By: Relevance
“…Some studies emphasize that frequent and excessive intake of fermentable sugars is the critical common predisposing factor for obesity and dental caries [24, 34].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies emphasize that frequent and excessive intake of fermentable sugars is the critical common predisposing factor for obesity and dental caries [24, 34].…”
Section: Discussionmentioning
confidence: 99%
“…Although not examined in the present study, a higher risk of dental erosion compared with dental caries among obese children has also recently been reported (38). From what can be concluded, a higher sugar intake may contribute to caries and obesity (39), and special consideration is called for to lead the children’s sense of taste to healthier habits for eating.…”
Section: Discussionmentioning
confidence: 99%
“…However, Qadri et al found that although iso-BMI (Body Mass Index) was associated with dental caries prevalence and severity, the association between caries increment and iso-BMI did not reach a statistical significance [49]. Overweight/obese children, however, acquired more additional carious lesions during the follow-up period than children with lownormal weight.…”
Section: Diet Dental Caries and Diseasesmentioning
confidence: 99%